Corona Enhancement and Mosaic Architecture for Prognosis and Selection Between of Liver Resection Versus Transcatheter Arterial Chemoembolization in Single Hepatocellular Carcinomas >5 cm Without Extrahepatic Metastases: An Imaging-Based Retrospective Study. Issue 2 (January 2016) - Li, Meng; Xin, Yongjie; Fu, Sirui; Liu, Zaiyi; Li, Yong; Hu, Baoshan; Chen, Shuting; Liang, Changhong; Lu, Ligong
Abstract : Abstract: Corona enhancement and mosaic architecture are 2 radiologic features of hepatocellular carcinoma (HCC). However, neither their prognostic values nor their impacts on the selection of liver resection (LR) versus transcatheter arterial chemoembolization (TACE) as treatment modalities have been established. We retrospectively analyzed 275 patients with a single HCC lesion >5 cm without extrahepatic metastasis treated with LR or TACE. In LR patients, the overall survival (OS) and time to progression (TTP) were compared between corona enhancement negative (corona−) versus positive (corona+) and mosaic architecture negative (mosaic−) versus positive (mosaic+) patients. Furthermore, by the combination of corona and mosaic, LR patients were divided into negative for both corona and mosaic patterns (LR−/−), positive for only 1 feature (LR+/−), and positive for both (LR+/+); their OS and TTP were compared to those of the TACE group. Cox regression was performed to identify independent factors for OS. In the survival plots for LR, corona− had better OS and TTP than corona+, and mosaic− had better OS than mosaic+. There was no significant difference in TTP between the subgroups. On Cox regression analysis, corona enhancement, but not mosaic architecture, was a significant factor for OS, whereas neither were a significant factor for TTP. In TACE patients, neither corona nor mosaic patterns had significant correlations with OS or TTP. In the whole population, LR−/ and LR+/− subgroups had similar OS, which was better than the LR+/+ and TACE groups. Moreover, LR−/− and LR+/− patients had better TTP than TACE patients, but there were no differences between the LR−/− versus LR+/−, LR−/ versus LR+/+, LR+/− versus LR+/+, and LR+/+ versus TACE groups. On Cox regression analysis, the presence of corona/mosaic patterns was an independent prognostic factor for OS. Our results showed that, for patients with a single HCC >5 cm without extrahepatic metastasis, corona and mosaic patterns are indicators of limited LR efficacy. When both of the features are present, TACE can be used instead of LR with no negative influence on survival.